Effect of episodic hypoxia on the susceptibility to hypocapnic central apnea during NREM sleep - Chowdhuri, Susmita (American Physiological Society, 2009)
We hypothesized that episodic hypoxia (EH) leads to alterations in chemoreflex characteristics that might promote the development of central apnea in sleeping humans. We used nasal noninvasive positive pressure mechanical ventilation to induce hypocapnic central apnea in 11 healthy participants during stable nonrapid eye movement sleep before and after an exposure to EH, which consisted of fifteen 1-min episodes of isocapnic hypoxia (mean O(2) saturation/episode: 87.0 ± 0.5%). The apneic threshold (AT) was defined as the absolute measured end-tidal Pco(2) (Pet(CO(2))) demarcating the central apnea. The difference between the AT and baseline Pet(CO(2)) measured immediately before the onset of mechanical ventilation was defined as the CO(2) reserve. The change in minute ventilation (V̇(I)) for a change in Pet(CO(2)) (ΔV̇(I)/ ΔPet(CO(2))) was defined as the hypocapnic ventilatory response. We studied the eupneic Pet(CO(2)), AT Pet(CO(2)), CO(2) reserve, and hypocapnic ventilatory response before and after the exposure to EH. We also measured the hypoxic ventilatory response, defined as the change in V̇(I) for a corresponding change in arterial O(2) saturation (ΔV̇(I)/ΔSa(O(2))) during the EH trials. V̇(I) increased from 6.2 ± 0.4 l/min during the pre-EH control to 7.9 ± 0.5 l/min during EH and remained elevated at 6.7 ± 0.4 l/min the during post-EH recovery period (P < 0.05), indicative of long-term facilitation. The AT was unchanged after EH, but the CO(2) reserve declined significantly from −3.1 ± 0.5 mmHg pre-EH to −2.3 ± 0.4 mmHg post-EH (P < 0.001). In the post-EH recovery period, ΔV̇(I)/ΔPet(CO(2)) was higher compared with the baseline (3.3 ± 0.6 vs. 1.8 ± 0.3 l·min(−1)·mmHg(−1), P < 0.001), indicative of an increased hypocapnic ventilatory response. However, there was no significant change in the hypoxic ventilatory response (ΔV̇(I)/ΔSa(O(2))) during the EH period itself. In conclusion, despite the presence of ventilatory long-term facilitation, the increase in the hypocapnic ventilatory response after the exposure to EH induced a significant decrease in the CO(2) reserve. This form of respiratory plasticity may destabilize breathing and promote central apneas.